2012
DOI: 10.1378/chest.11-0801
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cough With Disease Activity and Treatment With Cyclophosphamide in Scleroderma Interstitial Lung Disease

Abstract: Nonproductive cough is a characteristic symptom of interstitial lung diseases (ILDs), including scleroderma (SSc). In the Scleroderma Lung Study (SLS), a double-blind, randomized, placebo (PLA)-controlled trial of oral cyclophosphamide (CYC) administered for 1 year followed by an additional year of follow-up without treatment, 1 73% of the 158 study participants complained of cough at the time of enrollment, making it the second-most-common nonRaynaud symptom, exceeded only by dyspnea. After 12 to 18 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…These findings are consistent with previously reported international studies where cough was found to be a predictor of ILD activity and severity (51) , and both dyspnoea and bibasal crackles were predictors of FVC decline in SSc ILD patients (52) . Unfortunately due to lack of data, particularly with respect to grading of ILD severity on HRCT, further associations were not amenable to analysis.…”
Section: Interstitial Lung Disease Severity In Systemic Sclerosissupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previously reported international studies where cough was found to be a predictor of ILD activity and severity (51) , and both dyspnoea and bibasal crackles were predictors of FVC decline in SSc ILD patients (52) . Unfortunately due to lack of data, particularly with respect to grading of ILD severity on HRCT, further associations were not amenable to analysis.…”
Section: Interstitial Lung Disease Severity In Systemic Sclerosissupporting
confidence: 93%
“…Of interest in resource-poor settings, where HRCT (and possibly PFTs) may not be readily available, is the correlation between severity of lung fibrosis with clinical parameters at presentation -namely skin scores, dyspnoea and cough. Theodore et al, (2012) (51) found that cough correlated with severity of fibrosis, settled with treatment with cyclophosphamide, and returned with worsening disease activity.…”
Section: Interstitial Lung Disease Severity and Progression In Systemmentioning
confidence: 99%
“…Of note, patients with PAH may also have exertional dyspnea and fatigue and the clinician must keep both entities in mind when evaluating an SSc patient for dyspnea. Dry cough is often present, and may correlate with DLCO and dyspnea[24]. In the Scleroderma Lung Study, cough severity improved in patients treated with cyclophosphamide, but these improvements disappeared after two years of follow up[25, 26].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…In IPF, cough is associated with poor HRQoL and disease progression [35]. In CTD-ILD, the prevalence of cough has been reported to be as high as 73% [36] and is associated with a poor quality of life, and worse extent of lung fibrosis [36]. The mechanism of cough in ILD is poorly understood.…”
Section: Cough As An Outcome Measurementioning
confidence: 99%